Pengaruh Inflasi dan BI Rate Terhadap Volume Simpanan Masyarakat pada Bank Umum Pemerintah di Indonesia Periode 2013-2017 - Made Yuni Emitha Upadiyanti; Kompiang Bagiada; A. A Gede Agung Parameswara (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2018)
The aims of the research is to find out how the inflation and BI Rate influence on the Volume of Public Saving at Government Commercial Banks in the 2013-2017 period. The sample of research is use the government commercial banks in Indonesia which is recorded in Bank Indonesia that fulfilled the predetermined criteria as the sample. The data analysis was carried out by classical assumption and hypothesis testing using multiple linier regression methods. The result of the research is in partially, the inflation and BI Rate have a negative and significant effect. Simultaneously, the inflation and BI Rate, influence the volume of the public savings in government commercial bank significantly.